THE METACOGNITIVE SELF-REGULATION OF STUDENTS TOWARD ENGLISH LEARNING ACHIEVEMENT AT X1 SMPN 2 DUAMPANUA PINRANG - Purnama, Suci; Asriati, Sitti; Hamid, Sitti Maryam (English Language Teaching Methodology, 2025)
This study used a quantitative approach. Quantitative research is research that in the process uses a lot of numbers starting from data collection, data interpretation, and display of results. The samples in this study were 58 students of SMP Negeri 2 Duampanua who were sitting in class IX. The formulation of the problem in this study is "How is the students' metacognitive self-regulation on English  learning in class XI of SMPN2 Duampanua Pinrang?".Based on the results of the research conducted, the results of revealed that between the metacognitive variables of self-regulation and English learning achievement students had a significant positive effect with a significant value of 0.028 greater than 0.05, because the value of T-Table = 5.060 > from the value of F-table = 4.0129. Thus, Ha is accepted and Ho is rejected. Thus, the regression equation used can be applied in data analysis. So it can be concluded metacognitive self-regulation have a role in determining students’ English learning achievement of class IX students at SMPN 2 Duampanua Pinrang